2005
DOI: 10.1117/12.605757
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues in real-world implementation of structural health monitoring systems

Abstract: Currently, there exist several different types of structural health monitoring (SHM) systems that are in the stage of development and/or are being tested for use in real-world applications. For a number of years, Structural Health Monitoring (SHM) systems have demonstrated feasibility in laboratory and controlled testing environments. Acellent has been developing and testing strategies to bring the SHM field to the next level. These include issues involved with system installation, calibration, reliability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The performance and reliability of layered piezoelectric actuator/sensor networks was recently evaluated by Kusaka and Qing [70] and Beard et al [71,72] (see Stanford Multiactuator-Receiver Transduction (SMART) Layer Technology and Its Applications). In those efforts, the mechanical loading durability, environmental reliability, and overall system reliability of Acellent's Stanford multiactuator receiver transduction (SMART) layer technology [73] were studied, respectively.…”
Section: Reliability Of Layered Piezoelectric Actuator/sensor Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance and reliability of layered piezoelectric actuator/sensor networks was recently evaluated by Kusaka and Qing [70] and Beard et al [71,72] (see Stanford Multiactuator-Receiver Transduction (SMART) Layer Technology and Its Applications). In those efforts, the mechanical loading durability, environmental reliability, and overall system reliability of Acellent's Stanford multiactuator receiver transduction (SMART) layer technology [73] were studied, respectively.…”
Section: Reliability Of Layered Piezoelectric Actuator/sensor Networkmentioning
confidence: 99%
“…Testing results for the SMART Layer system were highlighted in that effort, where environmental conditions (temperature, moisture, chemical attack) were considered as well as mechanical shock/loading, and intense fatigue testing. In general, the results indicated that the layered piezoelectric actuator/sensor networks did not lose functionality for most realistic operational conditions [71]. The need for self-diagnosis, sensor redundancy, and environmental compensation was also discussed with regard to improving overall system reliability [72].…”
Section: Reliability Of Layered Piezoelectric Actuator/sensor Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 22 [49], in the active mode, an electric pulse is sent to a piezoelectric actuator that produces Lamb waves within the structure under evaluation. The array of piezoelectric sensors will pick up the resultant Lamb waves for processing and analysis.…”
Section: Piezoelectric (Pzt)-based Sensor Networkmentioning
confidence: 99%
“…This system uses a network of distributed piezoelectric sensors/actuators embedded on a thin dielectric carrier film called the SMART Layer R , see [3], [4]. The SMART Layer technology has both active and passive sensing capabilities via the embedded piezoelectric transducers, see Figure 3.…”
Section: A Shm Sensing Systemmentioning
confidence: 99%